When the East Meets the West: the Future of Traditional Chinese Medicine in the 21st Century - Jin QIU (康复学报)
Traditional Chinese medicine (TCM) has a history of thousands of years, is a very valuable treasure left by our ancestors, and there are many things which are worth our in-depth mining. But in the past hundreds of years, with the Western medicine came to our country, the debate of exchange, blending and comparison about Chinese and Western medicine culture is very common. In the forum, "Traditional Chinese medicine modernization can bring about medical rehabilitation?", which is presided by PU Muming, executive deputy editor of the National Scientific Review. Five distinguished guests from different fields discuss the subject about"Key features of traditional Chinese medicine", "Is traditional Chinese medicine pseudoscience?", "Modernization of traditional Chinese medicine", "Traditional Chinese medicine in the Chinese healthcare system", "Challenges in combining traditional Chinese medicine with Western science and medicine". The forum discuss that: a key aspect of TCM is its holistic perspective and personalized theranostics. Taking advantage of both TCM's holistic feature and technologies derived from Western science will benefit to the revival of Medicine. It's said that the 21st century is the century of compound medicine. We shouldn't place TCM and Western medicine in opposite roles. The key is to find a way to go about it. And it's very important to make sure that TCM and Western medicine complement each other. Since 2007, China has initiated an ambitious plan to modernize TCM. Since the implementation of the plan, two basic problems of TCM, such as effective ingredients and mechanism, have acquired significant outcome. TCM and Western medicine are equally important, which is the significant characteristic of the Chinese healthcare system and is the key feature of Chinese style solution for healthcare reform. TCM and Western medicine are originated from different cultural and historical contexts. So the perspectives are different, the language and mode of thinking are different. It's a big challenge to bridge those gaps.